Investigating the Effectiveness of Labor Market Interventions in Addressing Unemployment Challenges - Priyanto, Adi; Kahfi, Fahrul; Nazrun, Nazrun (Scieclouds Publishing, 2023)
This research focuses on the impact of a number of policies that exist in the labor market and seek to answer the following question: How successful are those policies to train the unemployed people, subsidize their wages, and briefly match them to jobs? In the context of the current study, a survey was carried out on 500 unemployed individuals following the use of a quantitative research design to determine their employment status before and after participation in the intervention program. Data collection included a structured employment outcome and demographic questionnaire alongside the secondary data from records of the official tertiary programmes for cross-checking. Data analyses, comprising of descriptive and ANOVA, established that employment result varied with the type of intervention, with skills training showing the most favourable results. In addition, the results show that successful labor market measures to promote employability depend on the design, which needs to be adjusted according to the target population. The current study enriches the existing literature by presenting findings on the effectiveness of the interventions and filling the gaps of the variability of the demographic characteristics of the subjects. Accordingly, future research for long term effect of such intervention is needed, and also ways it can be made more effective for diverse population groups.